Design estratégico, significação e relacionamento: repensando a educação a distância a partir do comportamento do professor e de efeitos de sentido - Reis, Gustavo Freitas (Universidade do Vale do Rio dos Sinos, 2015)
This research focuses on exploring ways in which Strategic Design may contribute to power the perception of proximity of students related to their teachers when reunited as actors of distance learning environments based on asynchronous video. The investigation observed the promotion of such effects from discourse and enunciation strategies, exploring the design related project- and metaproject-based possibilities on the demarcation of the teacher’s behavioral items, especially classified such as verbal immediacy or non-immediacy. Such elements may be put into practice by teachers with the objective of making their students, even at a distance, develop positive perceptions related to their instructors, impressions that are usually associated to the notion of proximity related to the concept of immediacy. Positive consequences from these perceptions are not limited to the relationship itself, but have the potential to trigger increments to the actors’ motivation, determination and enthusiasm levels and, consequently, lead to increments on teachers’ professional satisfaction and students’ learning, which result in benefits not only to the directly involved agents, but also to the educational institution that promotes their connections. In a perspective orientated by Strategic Design, such benefits may have their effects observed over the complete product-service-system characterized by the educational institution. The proposed research problem is naturally multifaceted, and the theoretical foundation choices reflect this characteristic. References from design research, with emphasis on design-driven innovation processes, were included, as well as references from linguistics, communication and social psychology fields. The presented results support the value proposition encapsulated by the primary objective and provide more solid foundations to rethink the teacher-student relationship from a design mindset.
Keywords: Design estratégico; Educação; Relacionamento; Comunicação; Significação; Strategic design; Education; Relationships; Communication; Signification; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial